PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA KARYAWAN PADA AJB BUMIPUTERA 1912 CABANG MATARAM - Baiq Ertin Helmida; Irianto Irianto (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
This study aims to: (1) examine the direct influence of motivation on performance; (2) examine the direct influence of motivation on job satisfaction; (3) examine the indirect influence of motivation on performance through job satisfaction; (4) Examine the direct influence of the work environment on performance; (5) Examine the direct influence of the work environment on job satisfaction; (6) Examine the indirect influence of work environment on performance through job satisfaction; (7) Examine the influence of job satisfaction on performance. This research was conducted in AJB Bumiputera 1912 Branch of Mataram with population of 50 people, the researcher took 45 people as the sample using purposive sampling technique. Data collecting technique were conducted by observation, interview and questionnaire.Analysis method using inferential statistic and path analysis. The results showed: (1) motivation directly has a significant influence on the employee performances; (2) Motivation directly has a significant influence on the employee satisfactions ; (3) Motivation indirectly has no significant influence on performance through job satisfaction. Thus job satisfaction does not mediate the influence of motivation on performance; (4) The work environment directly has a significant influence on the employee's performance; (5) The work environment directly has a significant influence on the employee satisfaction; (6) The work environment indirectly has no significant influence on performance through job satisfaction. Thus, job satisfaction does not mediate the influence of the work environment on performance; (7) Job satisfaction directly has a significant influence on employee performance